The Prevalence of Migraine in Iran: A Systematic Review and Meta-Analysis - Farhadi, Zeynab (Iran Red Crescent Med J, 2016)
CONTEXT: Migraine is a major dilemma and problem which affects public health and results to reduced quality of life. This study aimed to determine the prevalence of migraine in Iran. EVIDENCE ACQUISITION: A systematic search was conducted using Pub Med, Web of Science, Embase, Scopus, Ovid, Google Scholar, as well as Iranian databases including: MagIran, IranMedex and Scientific Information Databank, from 2000 to November, 2015. The Der-Simonian/Laird’s random-effects model, with a 95% confidence interval was employed to estimate the overall pooled prevalence. Heterogeneity was investigated using subgroup analysis based on sample size and time of study. RESULTS: Thirty studies comprising 33,873 participants met the inclusion criteria for the analysis. The overall prevalence of migraine in Iran was 14% (95% CI, 12% to 17%), respectively. The overall prevalence was (8%; 95% CI 6% to 11%) according to the international classification of headache disorders (ICHD-1), (17%; 95% CI 13% to 21%) according to ICHD-2, and (18%; 95% CI 7% to 30%) according to the other questionnaire for migraine screener (ID Migraine), respectively. Meta-regression demonstrated that the prevalence of migraine increased by year of publication and decreased by sample size. CONCLUSIONS: The prevalence of migraine in Iran, which was estimated as 14%, was similar or even higher than that reported world-wide. Migraine can have impact on the economic productivity of any country; therefore it is necessary to educate people on the early detection and the discovery of an effective treatment of migraine. More thorough review of further studies in this field is recommended.